2011
DOI: 10.1073/pnas.1019381108
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase-2 mediates cell survival through phosphorylation and degradation of inositol hexakisphosphate kinase-2

Abstract: The inositol pyrophosphate, diphosphoinositol pentakisphosphate, regulates p53 and protein kinase Akt signaling, and its aberrant increase in cells has been implicated in apoptosis and insulin resistance. Inositol hexakisphosphate kinase-2 (IP6K2), one of the major inositol pyrophosphate synthesizing enzymes, mediates p53-linked apoptotic cell death. Casein kinase-2 (CK2) promotes cell survival and is upregulated in tumors. We show that CK2 mediated cell survival involves IP6K2 destabilization. CK2 physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…4b). This result shows that InsP 6 K2 is also activated under this condition because InsP 6 K2 is reportedly phosphorylated and degraded by CK2 [18], which leads to a decrease in InsP 6 K2 activity.…”
Section: Insp 6 K2 and Cytoplasmic Tdp-43 Induced Depletion Of Akt Phmentioning
confidence: 84%
See 1 more Smart Citation
“…4b). This result shows that InsP 6 K2 is also activated under this condition because InsP 6 K2 is reportedly phosphorylated and degraded by CK2 [18], which leads to a decrease in InsP 6 K2 activity.…”
Section: Insp 6 K2 and Cytoplasmic Tdp-43 Induced Depletion Of Akt Phmentioning
confidence: 84%
“…CK2 phosphorylates TDP-43, alpha-synuclein, and other molecules in a strong manner [43]. InsP 6 K2 is reportedly phosphorylated and degraded by CK2 [18], which leads to a decrease in InsP 6 K2 activity. The hyperphosphorylation of the TDP-43 C-terminal fragment facilitates its disassociation from the aggregate, thereby promoting its degradation by the ubiquitin proteasome system and the removal of its remnants from the cell [44].…”
Section: Discussionmentioning
confidence: 98%
“…CSNK2A1 exerts its anti-apoptotic role by protecting regulatory proteins from caspase-mediated degradation [29]. In addition, this molecule promotes cell survival by activating the Akt and Wnt signaling pathway [30]. The high overexpression exhibited by ARHGDIA and CSNK2A1 makes them potential candidate biomarkers of toxicity.…”
Section: Proteins Involved In Programmed Cell Death (Apoptosis)mentioning
confidence: 99%
“…IP 6 is recognized as an important regulator of many cellular functions in animal cells, including signal transduction, cell proliferation, and differentiation (25). Recent study showed that CK2 mediates cell survival through phosphorylation of inositol hexakisphosphate kinase-2 by enhancing its ubiquitination (26). Previously, we have shown that nucleolar phosphoprotein 140 (Nopp140), which is a nucleolar protein, specifically binds to CK2α and inhibits its catalytic activity in vitro (27).…”
mentioning
confidence: 99%